2021
DOI: 10.1177/21582440211006136
|View full text |Cite
|
Sign up to set email alerts
|

The Virtue of School Leadership: Three Paths to Fulfilling Value Forms

Abstract: This study discusses the fulfillment of value forms by examining the virtue of school leadership. The virtue of school leadership stresses character traits in leaders that focus on the pursuit of excellence, appear as a value form, comprise paths to fulfilling values, reinforce leaders’ positive motivation, and foster reform in schools. To investigate this phenomenon, a qualitative method was adopted to interview 18 leaders from schools in northern Taiwan. The analysis of the findings suggests that staff who e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(60 reference statements)
0
4
0
1
Order By: Relevance
“…It is worth noting that while the study found that teachers in public schools in the DepEd Division of San Pablo City were generally highly motivated, there may be variations in motivation levels among individual teachers. Therefore, school leaders need to continue to monitor teacher motivation and provide support to ensure that all teachers are adequately motivated to deliver quality instruction and support student learning (Whang, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that while the study found that teachers in public schools in the DepEd Division of San Pablo City were generally highly motivated, there may be variations in motivation levels among individual teachers. Therefore, school leaders need to continue to monitor teacher motivation and provide support to ensure that all teachers are adequately motivated to deliver quality instruction and support student learning (Whang, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…When teachers are given autonomy to make decisions about curriculum, instruction, and assessment, they are more likely to feel a sense of ownership and investment in their work (Hargreaves & Fullan, 2020). Additionally, involving teachers in decision-making processes at the school level can promote a sense of shared responsibility and ownership for school improvement (Whang, 2021).…”
Section: Teachers' Leadership Practicesmentioning
confidence: 99%
“…No estudo, foi possível observar a relevância da capacidade do diretor exercer liderança, no sentido de influenciar pessoas positivamente, característica essencial para servir de exemplo de liderança empreendedora e orientar a equipe para o desempenho desejado (Whang, 2021); apoiar professores a superarem os seus desafios (Brasil, 2022); e criar uma cultura empreendedora na escola (Brasil, 2018). Do mesmo modo, também essencial, é a capacidade de automotivação do diretor, para seguir adiante em seus propósitos mesmo diante de frustrações impostas por fatores externos e barreiras criadas por forças internas contrárias.…”
Section: Apresentação E Análise Dos Resultadosunclassified
“…Academic staff and administrators at universities play a critical role in achieving the instructional, research, and public service goals of higher education. From an organizational and structural viewpoint, academic staff and administrators may be seen as two cultural groups that regularly engage and interact with one another, through which relationships are established and regenerated (Whang, 2021). Academic personnel and administrators, on the whole, respect and collegiality for each other's intellectual and professional accomplishments.…”
Section: Relationships With Managers and Colleaguesmentioning
confidence: 99%